Long-Term Dietary Strawberry, Spinach, or Vitamin E Supplementation Retards the Onset of Age-Related Neuronal Signal-Transduction and Cognitive Behavioral Deficits - Joseph, J. A. (J Neurosci, 1998)
Recent research has indicated that increased vulnerability to oxidative stress may be the major factor involved in CNS functional declines in aging and age-related neurodegenerative diseases, and that antioxidants, e.g., vitamin E, may ameliorate or prevent these declines. Present studies examined whether long-term feeding of Fischer 344 rats, beginning when the rats were 6 months of age and continuing for 8 months, with diets supplemented with a fruit or vegetable extract identified as being high in antioxidant activity, could prevent the age-related induction of receptor-mediated signal transduction deficits that might have a behavioral component. Thus, the following parameters were examined: (1) oxotremorine-enhanced striatal dopamine release (OX-K(+)-ERDA), (2) cerebellar β receptor augmentation of GABA responding, (3) striatal synaptosomal(45)Ca(2+) clearance, (4) carbachol-stimulated GTPase activity, and (5) Morris water maze performance. The rats were given control diets or those supplemented with strawberry extracts (SE), 9.5 gm/kg dried aqueous extract (DAE), spinach (SPN 6.4 gm/kg DAE), or vitamin E (500 IU/kg). Results indicated that SPN-fed rats demonstrated the greatest retardation of age-effects on all parameters except GTPase activity, on which SE had the greatest effect, whereas SE and vitamin E showed significant but equal protection against these age-induced deficits on the other parameters. For example, OX-K(+)-ERDA enhancement was four times greater in the SPN group than in controls. Thus, phytochemicals present in antioxidant-rich foods such as spinach may be beneficial in retarding functional age-related CNS and cognitive behavioral deficits and, perhaps, may have some benefit in neurodegenerative disease.